The Effect of Organizational Climate and Leadership Style on Turnover Intention through Job Satisfaction as an Intervening Variable: Pengaruh Iklim Organisasi dan Gaya Kepemimpinan Terhadap Turnover Intention Melalui Kepuasan Kerja sebagai Variabel Intervening - Natasya, Savira; Abadiyah, Rifdah (Indonesian Journal of Law and Economics Review, 2023)
This study aims to analyze the effect of organizational climate and leadership style on turnover intention through job satisfaction as an intervening variable at the Bengkel Rama Motor. The method used in this research is a quantitative approach. Sampling in this study was carried out by saturated sampling method, with the number of respondents as many as 72 employees of Bengkel Rama Motor. The data analysis technique used in this study uses path analysis using the Smart PLS version 3.3 program. The results of this study prove that organizational climate affects turnover intention, leadership style affects turnover intention, job satisfaction affects turnover intention, organizational climate affects job satisfaction, leadership style affects job satisfaction, organizational climate does not affect turnover intention through satisfaction work as an intervening variable, and leadership style has no effect on turnover intention through job satisfaction as an intervening variable.